Pengaruh Kompensasi Nonfinansial Terhadap Kinerja Tenaga Kesehatan: Apakah Motivasi dan Kepuasan Kerja Berperan Sebagai Mediator? - Yunita Andriani; Tatik Suryani (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – The high workload and complexity in Community Health Centres (Puskesmas) reduce motivation and job satisfaction, ultimately affecting health worker performance. Non-financial compensation, such as recognition, appreciation, career development, and a supportive environment, are key factors that can boost motivation and job satisfaction, offering an alternative strategy to improve performance. Aim – Analysing the effect of non-financial compensation on the performance of Puskesmas health workers, and testing the role of motivation and job satisfaction as mediating variables. Design / methodology / approach – This quantitative study used a survey of 204 health workers (general practitioners, dentists, nurses, and midwives with ≥1 year of service) from 15 Puskesmas in Surabaya, selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire and analysed with Structural Equation Modelling (SEM) via Smart-PLS 4.0. Results and Discussion – The results of data analysis shows that non-financial compensation has a significant positive effect on performance, motivation, and job satisfaction, motivation has a significant positive effect on performance, and job satisfaction has an insignificant effect on performance. The mediation test shows that motivation significantly mediates the effect of non-financial compensation on performance, while job satisfaction does not mediate the effect of non-financial compensation on performance. Conclusion - Non-financial compensation has a direct effect on performance and an indirect effect through the intermediary of motivation, but job satisfaction is unable to mediate the relationship. Research implication – This study provides a practical contribution for Puskesmas management in designing effective non-financial policy innovations that have a direct impact on health worker performance. Research Limitations – The sample was limited to health workers in 15 Puskesmas, so the results are not fully generalisable.